2018
DOI: 10.1177/0959683618782598
|View full text |Cite
|
Sign up to set email alerts
|

Paleotempestology database for the western North Atlantic basin

Abstract: Paleotempestology, the study of past tropical cyclone activity, has grown considerably over the past two decades, and there is now a relatively dense network of sites across the Western North Atlantic Basin providing records of past tropical cyclone variability. This paper presents a new database of paleotempestological records generated from 61 studies published between 1993 and 2018 for this region. A total of 266 data entries, consisting of the calibrated ages of individual tropical cyclone events and the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…The models were operated from 1 September 2002 to 31 August 2005. This period covered the highest storm surge height ever recorded in Halifax, Nova Scotia, between 1919 and 2020 (1.6 m; Oliva et al, 2018) that occurred on 29 September 2003 (Hurricane Juan; Figure 1a). Based on the core locations and possible bank sources, we selected the sediment dynamics analysis site on the nearest bank at 43.33°N, 62.98°W to the southeast of Core 93‐07 with a water depth of 105 m (Figure 1b).…”
Section: Methodsmentioning
confidence: 94%
“…The models were operated from 1 September 2002 to 31 August 2005. This period covered the highest storm surge height ever recorded in Halifax, Nova Scotia, between 1919 and 2020 (1.6 m; Oliva et al, 2018) that occurred on 29 September 2003 (Hurricane Juan; Figure 1a). Based on the core locations and possible bank sources, we selected the sediment dynamics analysis site on the nearest bank at 43.33°N, 62.98°W to the southeast of Core 93‐07 with a water depth of 105 m (Figure 1b).…”
Section: Methodsmentioning
confidence: 94%
“…and Ti is depleted in coarse-grained sediment fractions, Br/Ti relates to high magnitude storms that transport coarse sediment rich in marine organic matter into Lake Robinson (Oliva et al, 2018). In this way, increased magnitude and frequency of tropical cyclones was detected for CE 1475-1670, i.e.…”
Section: A C C E P T E Dmentioning
confidence: 92%
“…Another wind-related study tested long-term changes of tropical cyclone activity in the western North Atlantic region. At Robinson Lake, a lagoon at the Atlantic coast of Nova Scotia (Canada) and close to the north-western limit of tropical cyclone pathways, Br/Ti indicates past cyclone activity (Oliva et al, 2018). As Br is a proxy for marine organic matter (Ziegler et al, 2008) M A N U S C R I P T…”
Section: Palaeoseismic Studiesmentioning
confidence: 99%
“…Few studies have concentrated on the Caribbean basin off Central America (Denommee, Bentley, & Droxler, 2014;Dunning & Houston, 2011;McCloskey & Keller, 2009). Oliva, Peros, and Viau, (2017); Oliva, Viau, Peros, and Bouchard, (2018) in their overview from the western North Atlantic Basin found that out of nine studies on Central America, six were focused on Belize and none were specifically related to Honduras. Also, a review of the region by Adomat and Gischler (2017) suggests that certain time intervals saw an increase in the frequency of storm activity.…”
Section: Rainfall Patterns From the Mayan Classic Periodmentioning
confidence: 99%